Tantangan dan Prospek Pengembangan Arbitrase Online sebagai Alternatif Penyelesaian Sengketa dalam Era Digital - Yoga Subekti Nugroho (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
This article discusses the challenges and prospects associated with the development of online arbitration as an alternative method of dispute resolution in the digital era. Along with the advancement of information technology and rapid economic growth, the use of online arbitration is becoming increasingly relevant to address conflicts between parties involved in digital business transactions. The first challenge faced is the adjustment of laws and regulations that support the development of online arbitration. A clear legal framework is needed to ensure the validity and enforcement of online arbitration decisions across different jurisdictions. In addition, data protection and information security are important issues in online arbitration proceedings, given the digital and global nature of modern business transactions. The development prospects of online arbitration include the efficiency, affordability and flexibility of the dispute resolution process. It can expedite conflict resolution without the need for direct involvement in conventional courts, while minimizing the cost and complexity of the process. These advantages can increase business people's confidence in online arbitration as an effective solution.